Phytochemical and nutritional evaluation of Shivamodak granules - A polyherbal ayurveda formulation - Rajanish S Meti; Deepak P Chaudhari; Aboli Patil (Wolters Kluwer Medknow Publications, 2024)
Introduction: Modak is one among the effective Ayurvedic dosage forms. Modak has to be used in fresh form as it is unstable in longer duration and hence to overcome this demerit and also to make it palatable to children, one such preparation Shivamodak used for Karshya (undernutrition) in children has been prepared in granule form. Methods: There are no analytical standards available for Shivamodak in the Ayurvedic Pharmacopoeia of India. Hence, the present work was undertaken to evaluate the organoleptic characters, physicochemical, preliminary phytochemical, nutritional components, and high-performance thin-layer chromatography (HPTLC) analysis of Shivamodak granules. Results: organoleptic characters, namely color, odor, taste, and consistency; physicochemical parameters showed loss on drying (12% w/w), total ash value (4.50% w/w), acid insoluble ash (1.20% w/w), and water-soluble extractive and alcohol-soluble extractive (53.5% w/w and 24% w/w, respectively). The pH was 7.3. A preliminary phytochemical analysis is shown the presence of essential oil, alkaloid, tannin, volatile oil, ascorbic acid, and glycoside. A 92% of particles were passed through 10-20-sized mesh. Nutritional components showed protein (10.44% w/w), fat (7.41% w/w), and carbohydrate (34.79% w/w). HPTLC analysis yielded 9 bands at 254 nm. Conclusion: The study forms the first report on the studied parameters on Shivamodak granules.